2016
DOI: 10.1111/jcpt.12415
|View full text |Cite
|
Sign up to set email alerts
|

Antifactor Xa levels vs. activated partial thromboplastin time for monitoring unfractionated heparin. A pilot study

Abstract: Utilizing an anti-Xa protocol to monitor heparin infusion showed favourable results compared with utilizing an aPTT protocol by maintaining values within the therapeutic goal range. The most common discordant pattern in our study was a disproportionate prolongation of aPTT to anti-Xa values. Patients with discordant values presenting with high aPTT to normal anti-Xa values may have an increased risk of bleeding complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 19 publications
1
50
0
1
Order By: Relevance
“…Based on the limited SARS-CoV-2 data and our own experience, we suggest to monitor the heparin activity of UFH treatment based on anti-Xa levels with a target value of 0.3 -0.7 U/L in all patients with SARS-CoV-2 instead of treatment based on aPTT levels 5,6,7 .…”
Section: Accepted Articlementioning
confidence: 99%
“…Based on the limited SARS-CoV-2 data and our own experience, we suggest to monitor the heparin activity of UFH treatment based on anti-Xa levels with a target value of 0.3 -0.7 U/L in all patients with SARS-CoV-2 instead of treatment based on aPTT levels 5,6,7 .…”
Section: Accepted Articlementioning
confidence: 99%
“…While anti‐Xa activity was elevated after LMWH administration, an associated prolongation in APTT was also evident. In the literature, there were studies reporting that APTT and anti‐Xa activity did not correlate with one another in the UFH‐treated patients . In contrast, there is a paucity of data about the relationship between these two indices in the patients after LMWH administration, especially in the context of anticoagulation for haemodialysis.…”
mentioning
confidence: 99%
“…In the literature, there were studies reporting that APTT and anti-Xa activity did not correlate with one another in the UFH-treated patients. [4][5][6][7] In contrast, there is a paucity of data about the relationship between these two indices in the patients after LMWH administration, especially in the context of anticoagulation for haemodialysis. In this report, the data collected in our trials were re-examined to see if a meaningful correlation between APTT and anti-Xa activity existed in the dialysis patients who received LMWH as anticoagulation.…”
mentioning
confidence: 99%
“…Another study was done by Samuel et al (Samuel et al 2016) showed in their pilot study that when comparing aPTT and anti-Xa, results showed that therapeutic range (> 50-100% of the time) was achieved in only 5 (10%) patients in the aPTT group vs. 21 (57%) in the anti-Xa group; P < 0•01.…”
Section: Discussionmentioning
confidence: 99%